2013
DOI: 10.1002/cbic.201300124
|View full text |Cite
|
Sign up to set email alerts
|

A Click‐and‐Release Pyrrolysine Analogue

Abstract: What's the catch? A pyrrolysine analogue bearing a terminal alkyne and an ester functionality can be incorporated into recombinant proteins and render them amenable to capture by the click reaction and subsequent release through ester hydrolysis. The utility of this pyrrolysine-inspired technology is demonstrated for the identification of SUMOylation sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…In a follow-up, the authors replaced the lysine N -ε with an oxygen, substituting the ε-amide for a cleavable ester bond ( 106 ). 101 …”
Section: Non-sense Suppression With Orthogonal Aars/trna Pairs For Gementioning
confidence: 99%
“…In a follow-up, the authors replaced the lysine N -ε with an oxygen, substituting the ε-amide for a cleavable ester bond ( 106 ). 101 …”
Section: Non-sense Suppression With Orthogonal Aars/trna Pairs For Gementioning
confidence: 99%
“…They all worked as PylRS substrates and their incorporation into proteins allowed for site-selective modifications with azide via the Cu(I)-catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) reaction. [6870] Concurrent efforts by Chin et al revealed another two click substrates ( 12 – 13 ) of PylRS. Although their original goal was to select PylRS mutants that can selectively recognize 12 and 13 , the evolution resulted in the native enzyme.…”
Section: An Outstanding Genetic Code Expansion Toolmentioning
confidence: 99%
“…SUMOylation affects protein function in a variety of ways, including localization and stability . Although several approaches for site‐specifically SUMOylating proteins have arisen, and several investigators have globally controlled SUMOylation or turned it off at specific sites by mutating the acceptor lysine to arginine, conditional turn‐on of native SUMOylation sites in live cells with wild‐type (WT) SUMO1 has not been reported to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…While small molecules, siRNAs, proteins, and genetic approaches have been validated to turn off RanGAP1 SUMOylation with varying degrees of specificity, approaches for selective SUMOylation turn‐on remain rare and require either SUMO overexpression, mutations to the SUMO modifier, or may only be carried out in test tubes as opposed to live cells . We addressed this methodology gap through development of small‐molecule‐triggered SUMOylation via the endogenous conjugation machinery, an approach that is applicable to other post‐translational modifications (PTMs) as well.…”
Section: Resultsmentioning
confidence: 99%